2020
DOI: 10.3390/cells9081857
|View full text |Cite
|
Sign up to set email alerts
|

Role of Inflammasomes in HIV-1 and Drug Abuse Mediated Neuroinflammaging

Abstract: Despite the effectiveness of combined antiretroviral therapy (cART) in suppressing virus replication, chronic inflammation remains one of the cardinal features intersecting HIV-1, cART, drug abuse, and likely contributes to the accelerated neurocognitive decline and aging in people living with HIV-1 (PLWH) that abuse drugs. It is also estimated that ~30–60% of PLWH on cART develop cognitive deficits associated with HIV-1-associated neurocognitive disorders (HAND), with symptomatology ranging from asymptomatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 216 publications
(274 reference statements)
0
20
0
Order By: Relevance
“…Sil et al . 51 hypothesized that HIV-1 proteins and drugs of abuse cooperatively activate inflammasomes, leading to neuroinflammation and contributing to premature aging. Glial cell activation and subsequent cerebral scarring have been noted as a hallmark of neuroinflammation in the context of HIV 52 .…”
Section: Discussionmentioning
confidence: 99%
“…Sil et al . 51 hypothesized that HIV-1 proteins and drugs of abuse cooperatively activate inflammasomes, leading to neuroinflammation and contributing to premature aging. Glial cell activation and subsequent cerebral scarring have been noted as a hallmark of neuroinflammation in the context of HIV 52 .…”
Section: Discussionmentioning
confidence: 99%
“…The high production of IL1 β in abortive HIV infection via NLRP3-mediated caspase 1 activation remarkably contributes to sustained inflammation and disease progression [ 23 ]. This sustained inflammation is important in the clinical manifestation of cardiovascular diseases [ 24 ], neurological [ 25 ], and other inflammatory diseases in HIV infection. Recently, it was shown that HIV Tat proteins trigger NLRP3 and NLRC5 inflammasome activation in microglia cells surging the production of proinflammatory cytokines that contribute to sustained neuroinflammation and bystander damage [ 25 ].…”
Section: Nlrp3 Activation In Hiv Infectionmentioning
confidence: 99%
“…This sustained inflammation is important in the clinical manifestation of cardiovascular diseases [ 24 ], neurological [ 25 ], and other inflammatory diseases in HIV infection. Recently, it was shown that HIV Tat proteins trigger NLRP3 and NLRC5 inflammasome activation in microglia cells surging the production of proinflammatory cytokines that contribute to sustained neuroinflammation and bystander damage [ 25 ]. Furthermore, HIV infects and triggers bystander damage of astrocytes and neurons in the brain via the ROS pathway and virus-induced mitochondrial damage [ 26 ].…”
Section: Nlrp3 Activation In Hiv Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Drug abuse is intimately linked with HIV infection and HAND. Many drugs of abuse cause neurotoxicity and increase the susceptibility of the CNS cells to HIV infection by upregulating genes or proteins necessary for HIV transcription/replication [22][23][24][25]. Drug abuse in the context of HIV infection is extremely complicated, with many unknown variables.…”
Section: Introductionmentioning
confidence: 99%